2020
DOI: 10.1016/j.jcot.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic considerations in spine surgery: What orthopaedic surgeon should know!

Abstract: With clinical innovation and technological advancement, the paradigm of surgical procedures on the spine and spinal cord along with the perioperative management are rapidly evolving. Irrespective of different modes the anesthetic management of spine surgery is challenging in view of significant blood loss, prolong procedure, position-related complications, and complex pain management. The enhanced recovery after surgery (ERAS) for this kind of surgery is yet to be finalized. The aim of this article is to highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…[17][18][19] It is important to note that most studies published regarding spine ERAS pathways included patients undergoing either 1-level or 2-level surgery rather than complex spine surgeries including > 2 levels. 244 Recommendation: (1) Institutions may form a multidisciplinary team of experts for the following reasons (Class I, Level of Evidence C-EO):…”
Section: Continued Review Of Institutional Eras Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] It is important to note that most studies published regarding spine ERAS pathways included patients undergoing either 1-level or 2-level surgery rather than complex spine surgeries including > 2 levels. 244 Recommendation: (1) Institutions may form a multidisciplinary team of experts for the following reasons (Class I, Level of Evidence C-EO):…”
Section: Continued Review Of Institutional Eras Pathwaysmentioning
confidence: 99%
“…However, other studies found no decrease in length of stay18,21,22 and no reduction in 30-day readmission rates17 or 30-day complication rates 17–19. It is important to note that most studies published regarding spine ERAS pathways included patients undergoing either 1-level or 2-level surgery rather than complex spine surgeries including >2 levels 244…”
Section: Evidence-based Clinical Practice Guidelines and Recommendationsmentioning
confidence: 99%
“…When the patient is placed in the prone position for surgical procedures, the anesthesia provider must optimize care to avoid the problems with the airway management (potential displaced ETT), ventilation, hemodynamic instability, position-related injuries (e.g. postoperative visual loss-POVL, peripheral nerve injury (PNI), and spinal cord injury) [ 23 ]. During one-lung ventilation for thoracotomy, anesthesia providers should employ a protective ventilation strategy, which includes maintenance of low tidal volume (TV), low airway pressure, low positive end expiratory pressure (PEEP) and keep minimum oxygen (O 2 ) concentrations to avoid lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical advances in technology and improvement are now addressing a broader spectrum of diseases, from single-level decompression to multistage exhaustive reconstruction. The number of patients is rapidly increasing due to the epidemic of persistent low back pain and the emergence of surgical procedures that are minimally invasive 1. Given the higher patient tolerance, a secure and safe airway, with better surgical exposure under muscle relaxants, general anaesthesia (GA) is frequently recommended for all types of spinal surgical procedures.…”
Section: Introductionmentioning
confidence: 99%